Visual-Tactile Spatial Multisensory Interaction in Adults With Autism and Schizophrenia - Noel, Jean-Paul; Failla, Michelle D.; Quinde-Zlibut, Jennifer M.; Williams, Zachary J.; Gerdes, Madison; Tracy, John M.; Zoltowski, Alisa R.; Foss-Feig, Jennifer H.; Nichols, Heathman; Armstrong, Kristan; Heckers, Stephan H.; Blake, Randolph R.; et al. (Frontiers in Psychiatry, 2020)
Background: Individuals with autism spectrum disorder (ASD) and schizophrenia (SZ) exhibit multisensory processing difficulties and social impairments, with growing evidence that the former contributes to the latter. However, this work has largely reported on separate cohorts, introducing method variance as a barrier to drawing broad conclusions across studies. Further, very few studies have addressed touch, resulting in sparse knowledge about how these two clinical groups may integrate somatic information with other senses. Methods: In this study, we compared adults with ASD (n=29), SZ (n=24), and typical developmental histories (TD, n=37) on two tasks requiring visual-tactile spatial multisensory processing. In the first task (crossmodal congruency), participants judged the location of a tactile stimulus in the presence or absence of simultaneous visual input that was either spatially congruent or incongruent, with poorer performance for incongruence an index of spatial multisensory interaction. In the second task, participants reacted to touch in the presence or absence of dynamic visual stimuli that appeared to approach or recede from the body. Within a certain radius around the body, defined as peripersonal space (PPS), an approaching visual or auditory stimulus reliably speeds reaction times (RT) to touch; outside of this radius, in extrapersonal space (EPS), there is no multisensory effect. PPS can be defined both by its size (radius) and slope (sharpness of the PPS-EPS boundary). Clinical measures were administered to explore relations with visual-tactile processing. Results: Neither clinical group differed from controls on the crossmodal congruency task. The ASD group had significantly smaller and more sharply-defined PPSs compared to the other two groups. Small PPS size was related to social symptom severity across groups, but was largely driven by the TD group, without significant effects in either clinical group. Conclusions: These results suggest that: 1) spatially static visual-tactile facilitation is intact in adults with ASD and SZ, 2) spatially dynamic visual-tactile facilitation impacting perception of the body boundary is affected in ASD but not SZ, and 3) body boundary perception is related to social-emotional function, but not in a way that maps on to clinical status.